Control of vascular permeability by adhesion molecules - Sarelius, Ingrid H (Tissue Barriers, 2014)
Vascular permeability is a vital function of the circulatory system that is regulated in large part by the limited flux of solutes, water, and cells through the endothelial cell layer. One major pathway through this barrier is via the inter-endothelial junction, which is driven by the regulation of cadherin-based adhesions. The endothelium also forms attachments with surrounding proteins and cells via 2 classes of adhesion molecules, the integrins and IgCAMs. Integrins and IgCAMs propagate activation of multiple downstream signals that potentially impact cadherin adhesion. Here we discuss the known contributions of integrin and IgCAM signaling to the regulation of cadherin adhesion stability, endothelial barrier function, and vascular permeability. Emphasis is placed on known and prospective crosstalk signaling mechanisms between integrins, the IgCAMs- ICAM-1 and PECAM-1, and inter-endothelial cadherin adhesions, as potential strategic signaling nodes for multipartite regulation of cadherin adhesion.